Neutrophil Extracellular Traps Formation and Aggregation Orchestrate Induction and Resolution of Sterile Crystal-Mediated Inflammation - Li, Yanhong; Cao, Xue; Liu, Yi; Zhao, Yi; Herrmann, Martin (Frontiers in Immunology, 2018)
The formation of Neutrophil Extracellular Traps (NETs) to immobilize pathogens represents a novel antimicrobial strategy of the immune system. The microparticles related to human diseases are classified into endogenous microcrystals including monosodium urate (MSU), calcium pyrophosphate dihydrate (CPP), calcium carbonate (CaCO3), calcium phosphate (CaP), calcium oxalate (CaOx), cholesterol, and exogenous material like crystals from silica. Although microcrystals possess distinct compositions and shapes, they have a common characteristic: they stimulate neutrophils to release NETs. In low and high densities neutrophils form NETs and aggregated NETs (aggNETs) that reportedly orchestrate the initiation and resolution of sterile crystal-mediated inflammation, respectively. Here we summarize the different roles of NETs and aggNETs stimulated by the particles mentioned above in related inflammatory reactions. The NETosis-derived products may represent a potential therapeutic target in crystal-mediated diseases.